2018
DOI: 10.1111/sode.12296
|View full text |Cite
|
Sign up to set email alerts
|

Maternal responses to negative emotions and child externalizing behavior: Different relations for 5‐, 6‐, and 7‐year‐olds

Abstract: Emotional and behavioral maturity expectations increase as children transition to primary school; thus, maternal responses that support and encourage children's expression of negative emotion may not benefit school-age children as much as preschoolers. The current study explored a change in the utility of these maternal responses among 187 families (62 5-year-olds, 75 6-year-olds, and 50 7-yearolds). Mothers reported on their responses to children's negative emotions and children's externalizing and internaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…Collectively, mothers' reactions to and beliefs about children's emotions explained 9.5% of the variance in children's social affective skills. Consistent with prior findings in different samples (Dunsmore et al, ; Mirabile et al, ; Nelson & Boyer, ) and as reported elsewhere with this sample (Castro, Halberstadt, et al, ; Rogers et al, ), children of more supportive mothers had fewer social affective skills . Of note, mothers' unsupportive behaviors were not significant and remained so in all subsequent steps.…”
Section: Resultssupporting
confidence: 90%
“…Collectively, mothers' reactions to and beliefs about children's emotions explained 9.5% of the variance in children's social affective skills. Consistent with prior findings in different samples (Dunsmore et al, ; Mirabile et al, ; Nelson & Boyer, ) and as reported elsewhere with this sample (Castro, Halberstadt, et al, ; Rogers et al, ), children of more supportive mothers had fewer social affective skills . Of note, mothers' unsupportive behaviors were not significant and remained so in all subsequent steps.…”
Section: Resultssupporting
confidence: 90%
“…Both Mirabile et al () and Nelson and Boyer () present evidence for age‐related shifts in the utility of parents' reactions to children's negative emotions between early and middle childhood. Mirabile et al () show that supportive reactions are beneficial when children are young (ages 3–4) but not when children are older (ages 5–6).…”
Section: Evidence For Age‐related Shifts In the Utility Of Emotional mentioning
confidence: 98%
“…In the second article of the Quartet, Nelson and Boyer () utilized a cross‐sequential design with 5‐, 6‐, and 7‐year‐old children to test the longitudinal associations between mothers' supportive and nonsupportive reactions and children's problem behaviors 1 year later. Results from multigroup cross‐lagged path models demonstrated a shift in the function of mothers' nonsupportive reactions in predicting children's problem behaviors 1 year later in older compared to younger children.…”
Section: Evidence For Age‐related Shifts In the Utility Of Emotional mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, evidence suggests that parenting responses vary by type of difficult emotion expressed (e.g., sadness vs. anger), as well as gender of parent and child (Sanders, Zeman, Poon, & Miller 2015). The child's developmental stage will also greatly influence the types of parenting responses considered to be supportive (Mirabile, Oertwig, & Halberstadt 2018; Nelson & Boyer, 2018). For example, in infancy and early childhood, proximity‐based soothing and co‐regulation would be considered supportive.…”
Section: Gaps and Future Directionsmentioning
confidence: 99%